Circulating Aspergillus fumigatus DNA Is Quantitatively Correlated to Galactomannan in Serum - Alanio, Alexandre; Menotti, Jean; Gits-Muselli, Maud; Hamane, Samia; Denis, Blandine; Rafoux, Emmanuel; Peffault de la Tour, Régis; Touratier, Sophie; Bergeron, Anne; Guigue, Nicolas; Bretagne, Stéphane (Frontiers in Microbiology, 2017)
The performance of antigen galactomannan (GM) for diagnosing invasive aspergillosis (IA) is hampered by the occurrence of false-positive results. Quantitative PCR has been proposed to improve the diagnosis of IA. Therefore, we analyzed the value of performing a PCR test to the GM-positive serum sample. Using a quantitative PCR assay specific for Aspergillus fumigatus 28S ribosomal DNA, we retrospectively tested 422 GM-positive (Platelia Biorad kit) serum samples collected over one year from 147 patients. The cases were classified based on EORTC criteria as “proven”, “probable”, and “no–IA” before availability of the PCR results. After exclusion of 65 samples for non-reproducibility of GM positivity (n=62) or PCR inhibition (n=3), 75 (21.0%) of the remaining 357 samples were PCR positive. GM and fungal DNA showed a significantly positive correlation (p<0.0001, R2=0.27, slope=0.98±0.19). At least one PCR positive result was observed in 63.3% (31/49) of IA patients and in 13.2% (13/98) of non-IA patients (p<0.0001). The PCR positivity was also associated with the presence of other microbiological criteria among the 44 patients with IA and complete mycological workup (p=0.014), as well as a higher mortality rate at six months among the 135 patients with hematological conditions (p=0.0198). Overall, we found a quantitative correlation between serum GM and circulating DNA with an increased likelihood of IA when both were positive. A PCR positive result also supported a higher fungal load when GM was already positive. We advocate adding a PCR test for every confirmed GM-positive serum sample.